International business and tourism : global issues, contemporary interactions / edited by Tim Coles and C. Michael Hall. - Coles, Tim , ed. and C. Michael Hall.; Michael Hall, C. Michael (New York, NY, 2008)
Split into four separate sections, with introductions outlining the key themes in each, the book examines such important topics as
Keywords: Tourism; International trade